UGT1A1*6 mutation associated with the occurrence and severity in infants with prolonged jaundice - Yang, Zhe; Lin, Fen; Xu, Jia-Xin; Yang, Hui; Wu, Yong-Hao; Chen, Zi-Kai; Xie, He; Huang, Bin; Lin, Wei-Hao; Wu, Jian-Peng; Ma, Yu-Bin; Li, Jian-Dong; et al. (Frontiers in Pediatrics, 2022)
BACKGROUND: This study aimed to investigate the influence of a variant of the UGT1A1 gene on the occurrence and severity of prolonged jaundice in Chinese infants at term. METHODS: 175 infants with prolonged jaundice and 149 controls were used in this retrospective case-control study. The infants with prolonged jaundice were subdivided into the mild-medium and severe jaundice groups (TSB≥342µmol/L). The frequency and genotype distribution of the UGT1A1 and G6PD genes, and clinical parameters including sex, birth weight, delivery mode, gestational age, and feeding mode, were analyzed, and the differences in the parameters between the two groups were compared. RESULTS: The allele frequency of UGT1A1*6 in the prolonged jaundice group was higher than that in the control group. Similarly, it was also higher in the severe jaundice group than in the mild-medium jaundice group. Homozygous and heterozygous UGT1A1*6 were also found more frequently in the prolonged jaundice group than in the control group. Exclusive breastfeeding, homozygous and heterozygous forms of UGT1A1*6 were significant risk indicators for prolonged jaundice. Moreover, UGT1A1*6 was the best predictor of prolonged severe jaundice. CONCLUSION: UGT1A1*6 appears to be a risk factor for prolonged jaundice with hyperbilirubinemia in term infants of Chinese ancestry who are exclusively breastfed.